Psychological and social difficulties in young non-help-seeking adolescents at risk for psychosis: insights from a large cohort study - Teigset, Charlotte M.; Mohn, Christine; Mohn-Haugen, Caroline R.; Larøi, Frank; Rund, Bjørn Rishovd (Frontiers in Psychology, 2024)
Background This study used data from the Norwegian Mother, Father, and Child Cohort Study (MoBa), and explored the psychological and social challenges of 14-year-olds who report psychotic symptoms. Research on help-seeking youths indicates comorbid symptoms of depression, anxiety, and social deterioration, but less is known about non-help-seeking individuals who may not use healthcare services, possibly skewing comorbidity profiles. Also, findings suggest that adolescents manifesting psychotic symptoms refrain from pursuing help. This gap underscores the necessity of studying non-help-seeking adolescents to better understand their needs and the risks they face without intervention. Methods We analyzed responses from adolescents who completed the 14-year questionnaire in MoBa (N = 127), identifying those as at risk by their high scores on psychosis-risk items, within the top 0.4% (N = 58). Comparative analyses were conducted against matched controls to assess differences in psychological and social functioning (N = 69). Results Results indicated that the at-risk adolescents experience significantly more depression and anxiety and have lower self-esteem and poorer social functioning than controls. Social functioning parameters, including leisure activities, social competence, quality of parental relationship, and sense of school belonging, were significantly worse than those observed in controls. The results indicate a pronounced vulnerability among non-help-seeking adolescents at-risk, similar to issues seen in help-seeking youths. Conclusion These findings highlight the importance of early identification and intervention strategies that reach beyond traditional clinical settings, suggesting the efficacy of population or community-based screenings to prevent long-term adverse outcomes. The study proposes a broader understanding of psychosis risk, stressing the importance of inclusive approaches to support at-risk adolescents effectively.